Diabetes Insipidus—Treatment with 8-Lysine Vasopressin in a Nasal Spray - Chirman, Samuel B. (1964)
Synthetic 8-lysine vasopressin administered as a nasal spray to three patients with diabetes insipidus resulted in excellent control in one. In the other two it was of some value as therapy supplemental to pitressin tannate in oil. The patient who was adequately controlled with “spray therapy” alone required the sprays every three hours during the day, but none during the night.